Effects of pharmaceutical care on adherence and persistence to bisphosphonates in postmenopausal osteoporotic women - Lai, Pauline Siew Mei; Chua, Siew Siang; Chew, Y.Y.; Chan, S.P. (Wiley, 2011)
WHAT IS KNOWN AND OBJECTIVE: Studies have shown that comprehensive interventions by pharmacists can improve adherence and persistence to osteoporosis therapy, but the association between adherence and bone turnover markers (BTMs) has never been studied. Therefore, the aim of this study was to evaluate the effects of pharmaceutical care on medication adherence (and its effects on BTMs), as well as persistence of postmenopausal osteoporotic women to prescribed bisphosphonates. METHODS: A randomized controlled trial was conducted from 2005 to 2009 in the University Malaya Medical Centre, Malaysia. Inclusion criteria: postmenopausal osteoporotic women diagnosed with osteoporosis with a T-score </= -2.5 or who had a low-trauma fracture and prescribed weekly alendronate/risedronate. Intervention participants received counselling on osteoporosis, risk factors, lifestyle modifications, goals of therapy, side effects and the importance of adherence. Adherence was assessed at months 3, 6 and 12, and persistence at month 12. Feedback on BTMs was provided at months 4 and 7. The control group received no counselling. Two BTMs were used: serum C-terminal cross-linking telopeptide of type I collagen (CTX-I) and serum osteocalcin (OC). Main outcomes measured: medication adherence, BTMs and persistence. RESULTS AND DISCUSSION: Intervention participants who received pharmaceutical care reported significantly higher medication adherence at 6 (P = 0.015) and 12 months (P = 0.047) compared with the control group; but this effect was not shown by the BTMs. This is probably due to the long effect of bisphosphonates in bone. A significant difference was found between serum CTX-I and OC in identifying non-responders to anti-resorptive therapy (P < 0.001), indicating the usefulness of BTMs as an objective marker. However, pharmaceutical care did not affect persistence to osteoporosis therapy within a 1-year period log rank (Mantel-Cox) chi(2) = 0.496, P = 0.481. The proportion of participants who were persistent with bisphosphonate therapy after 12 months was 89.8% and 87.0% in the control and intervention group respectively. WHAT IS NEW AND CONCLUSION: The provision of pharmaceutical care improved medication adherence but not persistence. BTMs were not appropriate objective measures for assessing adherence to weekly bisphosphonates but were useful for identifying non-responders to treatment within 3-6 months, much earlier than using bone mineral density. The study indicates that pharmacists have a role in improving medication adherence, but its long-term effect on persistence warrants further studies with longer duration.